Proinflammatory Soluble CD40 Ligand Is Associated with the Systemic Extent of Stable Atherosclerosis - Pereira da Silva, T (2021)
Background and objectives: Polyvascular atherosclerosis is frequent and associated with a high cardiovascular risk, although the mechanisms regulating the atherosclerosis extent to single or multiple arterial territories are still poorly understood. Inflammation regulates atherogenesis and soluble CD40 ligand (sCD40L) is an inflammatory mediator associated with the presence of single-territorial atherosclerosis. We assessed whether the sCD40L expression is associated with the atherosclerosis extent to single or multiple arterial territories and with the atherosclerosis severity in different territories. Materials and Methods: We prospectively enrolled 94 participants with no atherosclerosis (controls, n = 26); isolated coronary atherosclerosis (group 1, n = 20); coronary and lower extremity (LE) atherosclerosis (group 2, n = 18); coronary and carotid atherosclerosis (group 3, n = 12); and coronary, LE, and carotid atherosclerosis (group 4, n = 18). Serum sCD40L levels were quantified. Results: The sCD40L levels (ng/mL, mean (standard deviation)) were 4.0 (1.5), 5.6 (2.6), 7.2 (4.2), 5.9 (3.7), and 5.1 (2.4) in controls and groups 1 to 4, respectively (ANOVA p = 0.012). In nonrevascularized patients, the sCD40L levels were significantly higher in group 2 than in group 1 and were correlated with the number of LE diseased segments. Prior LE bypass surgery was associated with lower sCD40L levels. Coexistence of coronary and LE atherosclerosis was independently associated with the sCD40L levels. Conclusions: The sCD40L levels were increased in stable atherosclerosis, particularly in polyvascular coronary and LE atherosclerosis. The number of LE diseased segments and prior LE revascularization were associated with sCD40L expression. To our knowledge, these are novel data, which provide insights into the mechanisms underlying multi-territorial atherosclerosis expression. sCD40L may be a promising noninvasive tool for refining the stratification of the systemic atherosclerotic burden.